1H NMR-based metabolomic study of the effects of flavonoids on citrinin production by Monascus. (November 2020) - He, Shanshan; Wang, Yanling; Xie, Jianhua; Gao, Heng; Li, Xiujiang; Huang, Zhibing
Graphical abstract: Highlights: Metabolomics study of the effects of flavonoids on citrinin production by Monascus. Thirteen metabolites involved association with the citrinin reduction mechanism. It was possible routes to reduce citrinin synthesis by addition flavonoids. This study will aid the development of citrinin-control methods. Abstract: Monascus comprises purple-red molds. Various compounds can be obtained from these species, including statins and food-safe yellow, red, and orange pigments. However, the secondary metabolite citrinin, a mycotoxin, is produced during the late stages of growth. Citrinin biosynthesis should be reduced to apply Monascus pigments safely. Fortunately, this can be achieved by the addition of flavonoids (genistein, daidzein, apigenin, and kaempferol). However, the effects of these flavonoids on other metabolites remain unknown. Here, we report a 1 H NMR-based multivariate metabolomic analysis of the effects of flavonoids on mycotoxin citrinin production by Monascus . Fifteen metabolites involved in lysine and arginine biosynthesis and alanine, aspartate, glutamate, biotin, arginine, proline, and glutathione metabolism were detected. The reduction in glutamate, aspartate, biotin, and 2-phosphoglycerate content suggested their association with the citrinin reduction mechanism. This study identifies the citrinin production pathway in Monascus and will aid in the development of citrinin-control methods.